Schema proposition model for NoSQL applications - Imam, A.A. (Springer Verlag, 2019)
This paper proposes a schema proposition model for physical and logical modeling of NoSQL (Not Only SQL) document-store databases. Unlike the traditional databases which are rigid in design, the NoSQL databases are flexible, scalable, and low-latent making them to house big data efficiently. However, issues such as dataset complexity coupled with programmersâ low competency are making database modeling and designing very challenging, especially in balancing the significant parameters like availability, consistency and scalability. The proposed model aims to address this balancing by abstractly proposing schemas to programmers with respect to user defined system requirements, Create, Read, Update and Delete (CRUD) operations, etc. Exploratory and experimental approaches were adopted in this research. System requirement formulas were introduced to compute the expected performance. A mini system was developed to validate the proposed model by comparing the manually generated schema to the schema generated through the proposed model. Results obtained indicated a significant improvement in the schema generated by the proposed model. Â© Springer Nature Switzerland AG 2019.